Studi Konservasi Timpakul dan Moluska Berbasis Pengetahuan dan Sikap Masyarakat Desa Pagatan Besar, Kalimantan Selatan - Hilda; Anang Kadarsah; Erma Agusliani (The Ethnobiological Society of Indonesia, 2021)
The knowledge and attitudes of the community will influence the success of timpakul and mollusc conservation in Pagatan Besar Village. This study aims to study the knowledge and attitudes of the community and to compare the level of knowledge and attitudes of the community regarding timpakul and mollusc conservation in Pagatan Besar Village. This research was conducted in Pagatan Besar Village with a total of 85 respondents. Data collection was done by direct interviews using a questionnaire with the help of the Google form application. This research data analysis using descriptive analysis and Chi Square analysis. The results showed that the level of community knowledge in Pagatan Besar Village was dominated by people who had sufficient knowledge, namely as much as 79%. The attitude of the community in Pagatan Besar Village is dominated by people who have a positive attitude, namely as much as 94%. Based on the Chi Square analysis, there is a relationship between knowledge and attitudes with the characteristics of research respondents (gender, profession, and place of residence) on the conservation of timpakul and mollusks in Pagatan Besar Village. It can be concluded that gender, profession, and place of residence influence people's knowledge and attitudes.